HUMAN RIGHTS AND THE GENEVA CONVENTIONS - A W Dahl (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2007)
Today, there are two distinct bodies of law namely Human Rights Law and International Law of Armed Conflict. The latter often referred to as International Humanitarian Law, since it aims at reducing suffering during armed conflict. The Geneva Conventions of 1949 have a prominent place within International Law of Armed Conflict. It is also important, because the biggest part of International Law of Armed Conflict is regulated in these Conventions. Although there is close relation between the two bodies of law, but there are some differences, in particular, in applicability of its norms. Human Rights Law applicable in peacetime while International Law of Armed Conflict applicable in wartime. This article explains those issues in brief.